Size Matters: Effects of Propagule Size on Dispersal in Rivers - Christopher R. Farrow; Loong‐Tak Lim; Todd J. Morris; Josef D. Ackerman (Water Resources Research)
Abstract Biological particles (e.g., bacteria, eggs, fruit/seeds and larvae) of a wide range of sizes (i.e., 10−6–10−1 m) are transported over various distances (i.e., 100–104 m) downstream in rivers. We examined the effects of propagule size on downstream dispersal by releasing biodegradable microbeads (density ∼ 1,200 kg m−3) of three size classes (∼150, 250, 350 μm) at the Speed River, Guelph, ON. Hitting distance estimates and longitudinal dispersion coefficients declined with particle size and were significantly different between 150 and 350 μm microbeads. The magnitude of these differences was relatively small (∼5 m) because of the slow velocity (9.5 ± 0.01 cm s−1) and low turbulence (shear velocity = 1.9 ± 0.13 cm s−1) in the river. We examined the dispersion of larval and juvenile unionid mussels (size range = 56–415 μm, 247.54 ± 60.38 [mean ± SD] μm, N = 174) across a broader range of flow conditions by applying laminar and turbulent flow models in three river reaches of increasing velocity and turbulence. Model results indicated that the dispersal of smaller larvae increased disproportionately with increasing water column turbulence. Given that the peak in the size frequency distribution of larvae and juveniles corresponded to Rouse numbers (ratio of gravitational settling to water column turbulence) P < 1, we suggest a trade‐off in propagule size in the taxon, whereby the increased dispersal of smaller juveniles may come at the cost of reduced settlement success in turbulent environments.